2D layered transition metal dichalcogenides (MoS2): Synthesis, applications and theoretical aspects. (December 2018) - Singh, Arun Kumar; Kumar, P.; Late, D.J.; Kumar, Ashok; Patel, S.; Singh, Jai
Graphical abstract: Abstract: Recently, graphene and other two-dimensional (2D) transition metal dichalcogenides (TMDCs) have been widely explored due to their unique optical, mechanical, electrical and sensing properties for versatile electronic and optoelectronic applications. The atomically thin layers of TMDC materials have shown potential to replace state-of-the-art silicon-based technology. Graphene has already revealed an excess of new physics and multifaceted applications in several areas. Similarly, mono-layers of TMDCs such as molybdenum disulfide (MoS2 ) have also shown excellent electrical and optical properties possessing a direct band-gap of ∼1.8 eV combined with high mechanical flexibility. In contrast to semi-metallic graphene, the semiconducting behavior of MoS2 allows it to overcome the deficiencies of zero-band-gap graphene. This review summarizes the synthesis of 2D MoS2 by several techniques, i.e., mechanical and chemical exfoliation, RF-sputtering, atomic layer deposition (ALD) and chemical vapor deposition (CVD), etc. Furthermore, extensive studies based on potential applications of MoS2 such as the sensor, solar cells, field emission and as an efficient catalyst for hydrogen generation has been included. Theoretical aspects combined with the experimental observations to provide more insights on the dielectric, optical and topological behavior of MoS2 was highlighted.